Not "Rambo," Not "Hero": The Principal as Designer, Teacher and Steward - Richard Andrews; Bill Berube; Margaret P. Basom (Educational Considerations, 1993)
If we are to create schools that are generative and proactive places designed to fulfill the dual purpose of enculturation and equal access to knowledge, we must attend to the leader behavior of school principals.